Análisis de la campaña comunicacional disruptiva en la tienda De Prati en el 2019 - Espinoza Troya, Dayana Yulexi (2020)
A case study is presented below that initially addresses Disruptive Communication Campaigns about their appearance and the objective for which this are implemented by companies. The research is developed around the De Prati department store, taking into consideration the campaigns published on its portals and public social networks, with the aim of assessing its contribution like a tool for the construction of citizenship. For this research, an observation sheet and an interview were applied like techniques implemented in the data collection procedure. The results of this case study indicate that effectively Disruptive Communication Campaigns influence consumer behavior, attitudes and ideas, hence the importance of De Prati store implementing this type of advertising. For this reason, it is vitally important that professionals in the marketing or advertising areas of Ecuadorian companies get involved with this new concept of campaign in order that they become interested in them and can take advantage of them from their role as commercial entities and later can contribute positively to the community.